Directions in Scholarship on American Women and Protestant Foreign Mission: Debates Over "Cultural Imperialism" - Shemo, Connie Anne (History compass, 2012)
This essay argues that scholarship on American women missionaries is at the forefront of reconceptualized visions of U.S. women’s history, the history of U.S. foreign relations and the boundaries of U.S. history. In the heyday of Protestant foreign mission in the 19th and early 20th century, women missionaries usually could not preach, and so were heavily involved in spreading Western education, Western medicine, and ideas about "domesticity." American women missionaries therefore were central actors in American cultural expansion, and in the spread of specific ideas about the empowerment of women abroad. Some scholars have therefore seen women missionaries as especially complicit in American cultural imperialism, while others have protested the portrayal of American women missionaries as cultural imperialists. Particularly in the last decade, however, scholars have focused on how people in the host cultures have interpreted and adapted the messages of American women missionaries. This has challenged the idea that American women missionaries unilaterally imposed American culture on the people among whom they worked, while still taking seriously the ways in which American women missionaries both contributed to and benefitted from American imperialism. The essay argues for the importance of embracing the complexity of American women missionaries - their simultaneous opposition to imperialism and racism and complicity with imperialist structures and drawing on ideologies of race. Ultimately, the essay argues, scholarship on American women missionaries makes an important contribution to our understanding contradictions inherent in American cultural outreach more broadly.